The Effect of Chemical Substance and Immersion Time to Tensile Strength of Bamboo Betung (Dendrocalamus asper) as Chemical Preservation Treatment - Afif Rizqi Fattah; Ken Ninez Nurpramesti Prinindya; Hosta Ardhyananta (IPTEK Journal of Proceedings Series, 2014)
Bamboo is one of the materials which availability is overflow and easy to renewable. However, in use of bamboo, it often degraded by biotic and abiotic factors. Preservation is required to keep service life from bamboo that more durable. This research aims to analyze tensile strength of bamboo after have chemical preservation treatment and weather. Bamboo which researched is bamboo Betung (Dendrocalamus asper). This research use a method as this. First, bamboo be cut into tensile test sample, then makes a preserve liquid borax 0,05 M in 1 liters of water, boric acid 0,05 M in 1 liters of water, and mixture borax liquid with boric acid, with volume increase of boric acid liquid in every borax liquid amount as 20, 40 and 60%. Then, bamboo immerse in preserve liquid. After that, do tensile test to bamboo sample without weathering, and bamboo sample with weathering. From the result of this research, chemical substance of preserve raise a tensile strength. More time of immersion, tensile strength is drop. Tensile strength of bamboo Betung has not decreased on three days of weathering.